Analysis and experimental study on servo dynamic stiffness of electromagnetic linear actuator. (15th April 2022) - Lu, Jiayu; Li, Bo; Ge, Wenqing; Tan, Cao; Sun, Binbin
Highlights: The transfer function from disturbance to position deviation is obtained. The influence of system parameters of the EMLA on servo dynamic stiffness is studied. The servo dynamic stiffness experiment setup is built based on the linear motor. Simulational and experimental results demonstrate the reliability of the analysis. Abstract: The electromagnetic linear actuator has been widely used in new energy vehicles, aerospace, and intelligent robots in recent years. However, its application especially in high-precision servo control system is limited due to the disadvantage of insufficient dynamic stiffness. In this paper, a theoretical model of servo dynamic stiffness of electromagnetic linear actuator was established through analyzing the definition of servo dynamic stiffness. And the influence of system parameters of the electromagnetic linear actuator on servo dynamic stiffness was studied based on the frequency analysis of the Bode diagram and the mathematical simulation of MATLAB/Simulink. In addition, an innovative servo dynamic stiffness measurement method for electromagnetic linear actuators was established in this paper. The experimental and simulation results showed that the larger the coil resistance and the mover's mass, the smaller the servo dynamic stiffness and the worse the anti-disturbance ability of the system; the greater the coil inductance and force-current constant, the greater the servo dynamic stiffness, and the better the system's anti-disturbance ability. The experimental results were consistent with the theoretical analysis results. This study provides a reference for improving the dynamic characteristics of electromagnetic linear actuator and paves the way for its practical application in the high precision systems.